2017
DOI: 10.1002/jclp.22440
|View full text |Cite
|
Sign up to set email alerts
|

“Are You Having Thoughts of Suicide?” Examining Experiences With Disclosing and Denying Suicidal Ideation

Abstract: A number of factors influence the accurate and inaccurate disclosure of suicidal ideation. Further research is needed to understand how to facilitate accurate disclosure of suicidal ideation across settings and populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 22 publications
4
80
0
Order By: Relevance
“…More work is needed to refine and develop behavioral proxies. Though individuals may be more willing to report their feelings of social isolation or perception of being a burden than suicidal ideation (Podlogar et al, 2015), individuals may still be reluctant to disclose this sensitive information due to stigma concerns (Anestis & Green, 2015; Corrigan & Watson, 2002; Hom, Stanley, Podlogar, & Joiner, 2017b; Podlogar et al, 2015). Implicit measurement of suicide-related constructs (e.g., through reaction time-based tasks) may be an effective strategy to circumvent these concerns (Nock & Banaji, 2007; Nock et al, 2010); though, more research is needed on this front, particularly with regard to their utility in military samples (Chiurliza et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…More work is needed to refine and develop behavioral proxies. Though individuals may be more willing to report their feelings of social isolation or perception of being a burden than suicidal ideation (Podlogar et al, 2015), individuals may still be reluctant to disclose this sensitive information due to stigma concerns (Anestis & Green, 2015; Corrigan & Watson, 2002; Hom, Stanley, Podlogar, & Joiner, 2017b; Podlogar et al, 2015). Implicit measurement of suicide-related constructs (e.g., through reaction time-based tasks) may be an effective strategy to circumvent these concerns (Nock & Banaji, 2007; Nock et al, 2010); though, more research is needed on this front, particularly with regard to their utility in military samples (Chiurliza et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were evident when suicide ideation was examined as target variable. Hom, Stanley, Podlogar, and Joiner () examined undergraduates who reported having suicide ideation and found that the main facilitator for revealing suicidal thoughts was knowing that someone would understand them. Relational factors, specifically perceived social support and relationship closeness, were also factors affecting the decision to share suicidal thoughts by individuals with serious mental illness (Fulginiti, Pahwa, Frey, Rice, & Brekke, ).…”
mentioning
confidence: 99%
“…Attitudes to seeking professional help for a serious emotional problem are significantly associated with future help‐seeking and treatment use (Mojtabai, Evans‐Lacko, Schomerus, & Thornicroft, ). Furthermore, once engaged with professionals, those with a lifetime history of suicidal behavior report increased honesty in interactions with mental health professionals as opposed to society in general (Hom, Stanley, Podlogar, & Joiner, ).…”
Section: Discussionmentioning
confidence: 99%